Pengembangan Sistem Informasi Kepegawaian Berbasis Website Dengan Menggunakan Metode Prototype (Studi Kasus : PT. Paramarta Development Malang, Jawa Timur) - Devi Septiani; Djoko Pramono; Nanang Yudi Setiawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
In this era of rapid technological development, information needs have become a necessity that must be conveyed quickly and easily. As one example, namely Paramarta Development, this private-owned company located in Malang and its surroundings, the company provides the sale and purchase of houses located in Malang City. This company has several business process activities, one of which is the employee business process activities. The business process that has been carried out is quite complicated, confusing, and does not yet have an application to support existing employee business process activities. After the researcher conducted an interview with the owner of the company, the researcher found several problems. The first is absence, the attendance is still using a checklist or direct signature, the second is the recruitment, for this problem the company still uses a brochure when a recruitment is being held, the third is an employee salary slip, for this problem it takes a long time. From the existing problems, researchers can draw conclusions, namely the need for a system. Researchers will carry out several development activities including: Designing an personnel information system based on the results of analysis and users, modeling object interactions into sequence diagrams, carrying out object models described in class diagrams, tables containing data storage, several interface designs, and some algorithm design. This staffing information system is a website-based information system and has several features including: login feature, can access employee data, add employees, add recruitment, employee salaries, employee absences, employee status, and performance results, for test results that have been conducted by researchers declared valid. Keywords: Paramarta Development, Application, Validate, Website, Personnel Information System.